we have that
2x + 1/4 y= 3 (equation A)
2/3 x - y = 6 (equation B)
Part a) The expressions that give the value of y are
equation A
2x + 1/4 y= 3-----> (1/4)y=3-2x------> y=4*(3-2x)----> y=12-8x
equation B
2/3 x - y = 6------> y=(2/3)x-6
the answer Part a) is
The expressions that give the value of y are
y=12-8x-------> equation A
y=(2/3)x-6-----> equation B
Part b) The solution for the given system
y=12-8x
y=(2/3)x-6
using a graph tool
see the attached figure
the solution is
x=2.08
y=-4.62
the answer Part B) is
x=2.08
y=-4.62